Proinflammatory cytokines and leptin are increased in serum of prepubertal obese children - Aygun, AD; Gungor, S; Ustundag, B; Gurgoze, MK; Sen, Y (Wiley, 2005)
It has not yet been shown in prepubertal children how cytokines, leptin, and body mass, as well as parameters of obesity are interrelated. The aim of this study was to explore the relation between circulating levels of some cytokines with leptin and body mass index. A case control study was carried out in obese children of both sexes. An obese group was carried out with 63 school prepubertal children and a control group comprised the same number of nonobese children paired by age and by sex. Mean serum leptin concentration was significantly higher in the obese children at 19.9 +/- 7.4 ng/mL, than the control group (7.9 +/- 5.1 ng/mL). Serum IL-1 beta, IL-6, and TNF-alpha levels were also significantly higher in the obese group than controls (33.0 +/- 8.9, 45.2 +/- 11.8, and 9.2 +/- 2.3 pg/mL, versus 3.6 +/- 1.0, 13.1 +/- 3.9, and 3.9 +/- 1.0 pg/mL, resp). In controversy, serum IL-2 level was diminished in the obese group as 0.4 +/- 0.1 versus 0.9 +/- 0.1 U/L. Obesity may be a low-grade systemic inflammatory disease. Obese prepubertal children have elevated serum levels of IL-1 beta, IL-6, and TNF-alpha which are known as markers of inflammation.
Keywords: Gene-Product; Resistance; Overweight; Endotoxin; Cachexia; Puberty; Sex; Age